Effect of Turmeric (Curcuma longa) Powder and Synbiotic as Alternative to Antibiotic Growth Promoter on Carcass Characteristics and Nutrient Utilization in Broiler Chicks - Shende, Kavita; Nagar, Manish Kumar; Garg, Shruti; Choudhary, Bherulal; Sharma, Rahul Kumar (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during August, 2021–September, 2021 at College of Veterinary and Animal Science, Udaipur, Rajasthan, India to investigate the effect of turmeric (Curcuma longa) powder and synbiotic as alternative to antibiotic growth promoter on carcass characteristics and nutrient utilization in broiler chicks. Total 150 day-old chicks were purchased and randomly divided into 5 treatments having 30 chicks in each group with three replicates of 10 chicks in each. The five dietary treatments were designated as T1 control group supplemented with basal diet, T2 group supplemented with antibiotic at 0.02% level, T3 group supplemented with turmeric at 0.5% level, T4 group supplemented with synbiotic at 0.05% level and T5 group supplemented with turmeric at 0.25%+synbiotic at 0.025% in the diet. Highly significant (p<0.01) effect was observed on dressing percentage and non-significant effect was observed on eviscerated weight percentage. Significant effect (p<0.05) was observed for liver weight per cent and non-significant effect was observed for heart, gizzard, giblet weight per cent, dry matter metabolizability and nitrogen balance among the treatment groups as compared to control group. However, numerically highest dry matter metabolizability was observed in T5 followed by T4, T3, T2 and T1. Numerically highest nitrogen balance was found in T5 and lowest was observed in T1 group i.e. control group. It can be concluded that as an alternative to antibiotics, turmeric plus synbiotic supplementation could be used to positively influence the carcass traits and nutrient utilization in broiler chicks.